Different response of hypothalamus and temporal cortex to intranasal insulin in rat model of sporadic Alzheimer's disease: Molecular and cell biology/neurodegeneration and neuroprotection. (7th December 2020) - Knezovic, Ana; Budisa, Stjepan; Andrilovic, Ana; Homolak, Jan; Perhoc, Ana Babic; Barilar, Jelena Osmanovic; Salkovic‐Petrisic, Melita
Abstract: Background: Sporadic Alzheimer's disease (sAD) is the most common form of dementia. Central administration of streptozotocin (STZ‐icv) has been shown to induce Alzheimer‐like changes and has been proposed as a non‐transgenic sAD animal model. Intranasal insulin administration is being investigated as a possible pharmacological treatment in order to reverse and ameliorate brain insulin dysfunction, but exact mechanism is not yet clear. Method: Male Wistar rats were given icv vehicle or STZ (3 mg/kg). Activation of c‐fos co‐localized with neuronal, astrocytic and microglial markers was evaluated in the brain 2 hours after intranasal insulin administration (2 IU), which was given 1 month after STZ. Western blot analysis of insulin receptor (IR) and postsynaptic marker (PSD95) were performed in hypothalamus (HPT) and temporal cortex (TC) 2h after intranasal insulin administration in STZ‐icv rat model. Spectrophotometry was used to measure glucose and β‐amyloid in plasma and CSF and glutamate and insulin concentration in brain tissue samples. Result: Intranasal insulin significantly increases c‐fos expression in TC only. C‐fos expression in TC was co‐localized with neuron marker, while in HPT was co‐localized also with microglial marker, especially with activated microglia in STZ‐icv rats. Glucose levels were found unaltered in plasma and CSF, while β‐amyloid concentration was found slightly increased after STZ and insulin administration. Increment of insulin concentration was found most pronounced in HPT of control animals after intranasal insulin (+289% vs CTR). Both insulin and STZ significantly decreases glutamate concentration in HPT (∼−92% vs CTR). treatments mostly s. At the level of IR and PSD95 expression STZ and insulin have opposite effects in HPT compared to TC. Conclusion: In this research, we have shown that STZ and insulin have different and opposite effects in the brain, showing distinct cell response to insulin depending on brain region in rat model of sAD. Financed by CSF projects IP‐09‐2014‐4639 and IP‐01‐2018‐8938. This publication was co‐financed by the Scientific Centre of Excellence for Basic, Clinical and Translational Neuroscience (project "Experimental and clinical research of hypoxic‐ischemic damage in perinatal and adult brain"; GA KK01.1.1.01.0007 funded by the European Union through the European Regional Development Fund) .